Chelating Properties of Delonix elata Against Cypermethrin Induced Oxitative Stress and Antioxidant Enzyme Activity in Cyprinus carpio (Linn) - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn the present investigation, the toxic effect of cypermethrin on antioxidant enzyme activity in fresh water fish Cyprinus carpio. Cypermethrin was applied 96 hrs LC50 (250Âµg/l), sub lethal concentration (120 hours 50Âµg/l). The fish were treated with cypermethrin for five days, after that at the end of the fifth day treated fish were separated into two group one group is feed with Delonix elata supplementary fed for five days, organs like gill, liver and kidney were examined 24, 48, 72, 96 and 120 hours The antioxidant enzymes like catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (Gpx), Lipid peroxidation (TBARS) level changes occurs due to toxic effect of cypermethrin. Antioxidant enzymes are biomarkers used to indicating the cypermethrin toxic effect. SOD and CAT are decreased during exposure period. TBARS level increased negative correlation was observed in the treated group.GPX level increased in the treated group. In the recovery group Novelties antioxidant enzymes were increased and TBAR activity was decreased. Present study to know the toxic effect of cypermethrin on Cyprinus carpio fish and chelating property of Delonix elata supplementary feed.